Program Pemberantasan Buta Huruf Aksara Arab (Huruf Hijaiyah) dan Indonesia di Dusun Karang Kurian Barat Desa Kediri Kecamatan Kediri Kabupaten Lombok Barat - Moh Zarkani (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2026)
This service aims to make the people of Karang Kuripan Barat Hamlet, Kediri Village, Kediri District, West Lombok Regency 'literate' in Indonesian and Arabic. The community is expected to be able to read the Indonesian language well so that they can quickly obtain information related to regional potentials through various articles, books, and other sources. As a medium for understanding the religion of teaching Arabic, in this case, learning to read the Holy Qur'an is an obligation for the people of Molantadu Village, who are 100% Muslim. This service activity applies different learning methods adapted to the objectives of each exercise. Eradication of Indonesian and Arabic scripts using the Iqra method is